2011
DOI: 10.1142/s021881041100559x
|View full text |Cite
|
Sign up to set email alerts
|

Hand Infection in Diabetic Patients

Abstract: The diabetic hand infection is less reported in the literature. Therefore, it is easily ignored and underestimated resulting in increased morbidity among the diabetic population. Diabetic hand is a rapid in progression, extensive and severe tissue destruction. We analyze the clinical course and outcome of hand infection in diabetic patients. We reviewed all the admissions with hand infection from January 2006-April 2010. Thirty-seven patients were found with associated diabetes mellitus. The demographic data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 15 publications
0
41
0
3
Order By: Relevance
“…In detail, the study showed that beside cardiovascular causes and cancer, infectious diseases substantially contribute to the reduced life expectancy of diabetic people. [1,2,15,16] Diabetics were prone to suffer from infections, the mechanisms of which may be as follow: [17][18][19] 1. The body's defense system was weakened: Each stage of the body's defense to invading microorganisms was suppressed in diabetics, including leukocyte chemotaxis, phagocytosis, weakened intracellular bactericidal effect, neutralized toxin, decreased serum opsonin and cellular immune function, etc., 2.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, the study showed that beside cardiovascular causes and cancer, infectious diseases substantially contribute to the reduced life expectancy of diabetic people. [1,2,15,16] Diabetics were prone to suffer from infections, the mechanisms of which may be as follow: [17][18][19] 1. The body's defense system was weakened: Each stage of the body's defense to invading microorganisms was suppressed in diabetics, including leukocyte chemotaxis, phagocytosis, weakened intracellular bactericidal effect, neutralized toxin, decreased serum opsonin and cellular immune function, etc., 2.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, the numerical information found for all data was given in proportion to the total number of patients whose data were available. A total of 32 studies were included in the analysis (1,(5)(6)(7).…”
Section: Methodsmentioning
confidence: 99%
“…Meist sind es kleine Traumata mit kleineren Wunden, die zur Infektionen der Hand führen [4]. Infektionen der Hand haben ein sehr variables Erscheinungsbild von kleinen lokalen bis hin zu rapiden progressiven Verläufen [5]. Aufgrund der komplexen Anatomie der Hand mit ihren Kompartimenten, die durch bradytrophe Verteilungsräume mit limitierter Infektabwehr sowie Kommunikation wichtiger funktioneller Strukturen gekennzeichnet ist, kann eine Infektion zu erheblichen Funktionseinbußen führen bzw.…”
Section: Einführungunclassified